(untitled) (Global Journal of Management and Business Research, 2020)
The study examined the effect of Boko Haram insurgency in the North East on the socioeconomic activities of Nigeria. Ex-post facto research design as the observations was used in the research to establish the relationship between the variables. The study made use of secondary data covering a period of twenty years; were 10 years were from 1994-2003 before the insurgency and 10 years were from 2004-2013 during the insurgency. The data from this study were obtained from World Bank on agricultural value added percentage of GDP from 1994 to 2013 a period of twenty (20) years to determine the extent of agricultural contributions to Gross Domestic Product (GDP) in Nigeria. It is necessary to use this data that had been generated to show the time series effect. ARIMA statistical method of analysis was adopted with the aid of Statistical Package for Social Sciences (SPSS) to test the hypothesis. It was found out that the sects#x2019; activities in the North East had significantly affected the socioeconomic activities. The general conclusion was that Boko Haram insurgency in the North East had effect on socioeconomic activities of Nigeria. This study recommended that the federal government should embrace negotiation with the group since they ready to dialogue with the federal government but this can only be actual if the rebel group within the government cycle, which are ever ready to sabotage the strategy, are fished out, dislodged and prosecuted accordingly.